A genre and discourse-based examination of audio commentary. (15th August 2021) - Denny, Melody
Abstract : Providing comments on student writing is one of the most important, difficult, and time-consuming activities instructors undertake. Many studies have examined written feedback, and much research has shown the problems associated with this form, ranging from time spent providing thoughtful feedback to students' confusion about the commentary. Some instructors have used audio commentary to address these issues. Audio commentary has been researched for years; the results have indicated that students prefer audio commentary, and it is perceived as more personal and positive by instructors and students. To date, little research has looked closely at audio commentary to understand if or how it might differ from written in form and function. This research uses as multicase approach and genre analysis to examine the organisational moves and discourse analysis uncover why audio commentary is perceived differently by both producers and consumers of this genre. Results show that audio commentary does not differ in form or function from its written counterpart, but metadiscursive features may play a role in how the genre is perceived by both instructors and students, providing real evidence of how audio commentary is different from written.